European sea bass brain DLB-1 cell line is susceptible to nodavirus: A transcriptomic study. Issue 86 (March 2019) - Chaves-Pozo, Elena; Bandín, Isabel; Olveira, José G.; Esteve-Codina, Anna; Gómez-Garrido, Jèssica; Dabad, Marc; Alioto, Tyler; Ángeles Esteban, M.; Cuesta, Alberto
Abstract: Viral diseases are responsible for high rates of mortality and subsequent economic losses in modern aquaculture. The nervous necrosis virus (NNV) produces viral encephalopathy and retinopathy (VER), which affects the fish central nervous system. It is considered one of the most serious viral diseases in marine aquaculture, the European sea bass ( Dicentrarchus labrax ) being amongst the most susceptible. We have evaluated the European sea bass brain derived cell line (DLB-1) susceptibility to NNV genotypes and evaluated its transcriptomic profile. DLB-1 cells supported NNV gene transcription and replication since strains belonging to the four NNV genotypes produce cytopathic effects. Afterwards, DLB-1 cells were infected with an RGNNV strain, the one which showed the highest replication, for 12 and 72 h and an RNA-seq analysis was performed to identify potential genes involved in the host-NNV interactions. Differential expression analysis showed the up-regulation of many genes related to immunity, heat-shock proteins or apoptosis but not to proteasome or autophagy processes. These data suggest that the immune response, mainly the interferon (IFN) pathway, is not powerful enough to abrogate the infection, and cells finally suffer stress and die by apoptosis liberating infective particles. GO enrichment also revealed, for the first time, the down-regulation of terms related to brain/neuron biology indicating molecular mechanisms causing the pathogenic effect of NNV. This study opens the way to understand key elements in sea bass brain and NNV interactions. Highlights: European sea bass DLB-1 brain cell line is susceptible to all nodavirus genotypes. NNV infection induces heat-shock and immunity pathways. Viral infection affects cytoskeleton and apoptosis genes but no autophagy. NNV infection affects neuron and brain pathways.